Mapping of credit risk management research in islamic banks: A bibliomatric study - Ainiyah, Rizka Nur (Maliki Interdisciplinary Journal, 2025)
Credit risk management is one of the important elements in the operation of Islamic banks, which has unique challenges because it must comply with Islamic principles. This study aims to map the development of literature related to credit risk management in Islamic banks using a bibliometric approach. Data were obtained from Sinta-accredited national journals through the Garuda and Google Scholar platforms, analyzed using VOSviewer, Microsoft Excel, and Mendeley Desktop software. The results show that there were 31 publications related to this topic during the period 2017–2024. Bibliometric visualization identified eight main clusters with 52 items that describe research themes, including the relationship between credit risk and bank health, liquidity risk management, financial indicators such as the capital adequacy ratio (CAR) and return on assets (ROA), and the differences between Islamic and conventional banks. This study reveals that bibliometric analysis provides in-depth insights into research trends, patterns, and contributions in this field, helping to identify key challenges and opportunities for developing credit risk management in Islamic banks. These findings can serve as a guide for researchers and policymakers to develop innovative and sharia-compliant risk management strategies, in order to support the sustainability of Islamic banking globally.